How do trained panelists characterize baby leafy greens? A comparison of descriptive analysis and Napping. Issue 1 (21st December 2021) - O'Brien, Regina; Simon, James E.; Tepper, Beverly J.
Abstract : Abstract: Baby leafy greens are one of the fastest growing segments of the salad green market. Baby leafy greens are generally more mild tasting than their fully‐mature counterparts. Nevertheless, a diversity of plant species can be grown as baby greens, which exhibit a wide range of sensory attributes. Sensory profiles of baby leaf varieties have not been well described in the literature. This study aimed to describe the differences between several baby leafy green varieties from the plant family Brassicaceae and those which were non‐ Brassicaceae, and to compare two descriptive methods, traditional descriptive analysis (DA) and Napping, a rapid profiling technique. Both methods used the same trained panelists. In the first study, the panel ( n  = 11) developed a lexicon for and evaluated four samples grown in a controlled aeroponic environment. In the second study, 12 commercially available samples were evaluated with DA ( n  = 8) and Napping ( n  = 11). Panelists identified differences in the pungency, bitterness, and ''green'' attributes across all samples. Principal component analysis (PCA) was used to model associations between the samples and the sensory attributes. The PCA extracted three factors. PC1 ranged from pungent qualities to sweet/grassy, PC2 included green color, and PC3 included saltiness and sourness. The Napping showed similar sample separation (RV = 0.67), but included relevant textural terms (''chewy''; ''rubbery'') not used in the DA. The current lexicon can be applied to a large range of baby leafy greens. Napping showed good correspondence with DA and can be deployed with agricultural products where time and other resources may be limited. Practical Application: Sensory evaluation methods have traditionally been applied in the food industry with processed products.While traditional methods such as descriptive analysis have been used to profile products, rapid and inexpensive profiling methods should be screened for their value in describing agricultural products. The results of this study can be applied to breeding and grow‐out programs to aid in optimization of the processing, storage, and quality control for the rapidly expanding baby leafy green market.